PENGARUH AGEN SOSIALISASI TERHADAP POLA PENCARIAN PENGOBATAN MAHASISWA RUMPUN FAKULTAS NON-EKSAKTA UNIVERSITAS SUMATERA UTARA DI KOTA MEDAN TAHUN 2013 - Alam Bakti Keloko; Syarifah Harahap; Rifandi Raflis (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Health development aims to increase awareness, willingness and ability of each person to realize the degree of public health as high. Socialization is the process through which a child learns to be a participating member of society. Through this learning process one can take decisions in determining the searching pattern of medical treatment through family, playmate, school , and mass media, but schools are not included in this research due to non-exact student do not learn about health . This research was conducted to determine the influence of socialization agents on the searching pattern of medical treatment on clumps student non-exact faculty of University of Sumatera Utara in Medan in 2013. This research is using quantitative research methods. The data was collected through direct interviews with respondents. The population of this research were all student of non-exact faculty year 2010-2012 of University of Sumatera Utara by 10.784 people, and the sample size were 95 people taken with Proportional Random Sampling methods. The results showed male respondents (46.3%), female (53,7%), age 18 (14,7%), age 19 (18,9%), age 20 (30,5%), age 21 (26,3%), age 22 (9,5%), Faculty of Social and Political Sciences (29,5%), School of Law (20,0%), Faculty of Humanities (17,9%), Faculty of economics (32,6%). Statistical test of bivariate analysis showed that family were not related with students searching pattern of medical treatment (p=0,099>0,05), playmate were related with students searching pattern of medical treatment (p=0,01<0,05), mass media were not related with students searching pattern of medical treatment (p=0,420>0,05). Statistical test of multivariat showed that family were not influence students searching pattern of medical treatment (p=0,105>0,05), playmate were influence students searching pattern of medical treatment (p=0,01<0,05) . Students of non-exact faculty of University of Sumatera Utara needs to improve the search of information about searching pattern of medical treatment for himself and to influence his friends as an agents of socialization. University of Sumatera Utara also need to provide information about searching pattern of medical treatment for students . Keyword: agents of socialization, searching pattern of medical treatment